Low cost methods used to create 3D models - Chmurzyńska, Agnieszka; Hejbudzka, Karolina; Dumalski, Andrzej (International Conference “Environmental Engineering”, 2017)
During the last years the softwares and applications that can produce 3D models using low-cost methods have become very popular. What is more, they can be successfully competitive with the classical methods. The most well known and applied technology used to create 3D models has been laser scanning so far. However it is still expensive because of the price of the device and software. That is why the universality and accessibility of this method is very limited. Hence, the new low cost methods of obtaining the data needed to generate 3D models appeare on the market and creating 3D models have become much easier and accessible to a wider group of people. Because of their advantages they can be competitive with the laser scanning. One of the methods uses digital photos to create 3D models. Available software allows us to create a model and object geometry. Also very popular in the gaming environment device – Kinect Sensor can be successfully used as a different method to create 3D models. This article presents basic issues of 3D modelling and application of various devices, which are commonly used in our life and they can be used to generate a 3D model as well. Their results are compared with the model derived from the laser scanning. The acquired results with graphic presentations and possible ways of applications are also presented in this paper.
Keywords: 3D model; sensor Kinect device; laser scanning